Energy Consumption, Economic Growth and Environmental Degradation in 4 Asian Countries: Malaysia, Myanmar, Vietnam and Thailand - Phrakhruopatnontakitti, Phrakhruopatnontakitti; Watthanabut, Busakorn; Jermsittiparsert, Kittisak (International Journal of Energy Economics and Policy, 2020)
This paper examines dynamic causal relationships between pollutant emissions, energy consumption and output for a panel of 4 Asian (MMVT) countries over the period 1971–2005, except for Vietnam (1990–2005). In long-run equilibrium energy consumption has a positive and statistically signiï¬cant impact on CO2 emissions. In the short term, changes in emissions are driven mostly by the error correction term and short term energy consumption shocks, as opposed to short term output shocks for each country. Short-term deviations from the long term equilibrium take from 0.77 years (Myanmar) to 4.84 years (Malaysia) to correct. The panel causality results indicate there are energy consumption–emissions bidirectional strong causality and energy consumption–output bidirectional long-run causality, along with unidirectional both strong and short-run causalities from emissions and energy consumption, respectively, to output. Overall, in order to reduce CO2 emissions and not to adversely affect economic growth, increasing energy supply investment and energy efï¬ciency, and stepping up energy conservation policies to reduce unnecessary wastage of energy can be initiated for energy-dependent MMVT countries. Keywords: CO2 emission, Error Correction Model, Malaysia, Myanmar, Vietnam and Thailand JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.9229